Angiogenesis and Re-endothelialization in decellularized scaffolds: Recent advances and current challenges in tissue engineering - Mazloomnejad, Radman; Babajani, Amirhesam; Kasravi, Mohammadreza; Ahmadi, Armin; Shariatzadeh, Siavash; Bahrami, Soheyl; Niknejad, Hassan (Frontiers in Bioengineering and Biotechnology, 2023)
Decellularization of tissues and organs has recently become a promising approach in tissue engineering and regenerative medicine to circumvent the challenges of organ donation and complications of transplantations. However, one main obstacle to reaching this goal is acellular vasculature angiogenesis and endothelialization. Achieving an intact and functional vascular structure as a vital pathway for supplying oxygen and nutrients remains the decisive challenge in the decellularization/re-endothelialization procedure. In order to better understand and overcome this issue, complete and appropriate knowledge of endothelialization and its determining variables is required. Decellularization methods and their effectiveness, biological and mechanical characteristics of acellular scaffolds, artificial and biological bioreactors, and their possible applications, extracellular matrix (ECM), surface modification, and different types of utilized cells are factors affecting endothelialization consequences. This review focuses on the characteristics of endothelialization and how to optimize them, as well as discussing recent developments in the process of re-endothelialization.